Improving Youths' Perceptions of Law Enforcement: Results From an Experimental Design in Two Cities. (August 2023) - Sheeran, Alyssa M.; Freiburger, Tina L.; Knoche, Victoria A.
This study examined the effectiveness of Students Talking it Over with Police (STOP) to improve youth's perceptions of the police, perceptions of procedural justice, willingness to cooperate with police, willingness to file a police report, and knowledge about how to file a police report. An experimental design was employed in Racine, WI and St. Louis, MO and found that STOP was effective in improving perceptions of the police, perceptions of procedural justice, and willingness to cooperate with police in both locations; limited evidence was found in youth's willingness to file and knowledge about how to file a police report. Analyses in St. Louis found that race/ethnicity and grade level were associated with knowledge about how to file a police report.